Treatment of bacteriobilia decreases wound infection rates after pancreaticoduodenectomy. Issue 6 (29th August 2013) - Mohammed, Somala; Evans, Charity; VanBuren, George; Hodges, Sally E.; Silberfein, Eric; Artinyan, Avo; Mo, Qianxing; Issazadeh, Medhi; McElhany, Amy L.; Fisher, William E.
Abstract Background Although mortality following pancreaticoduodenectomy is decreasing, postoperative morbidity remains high. It was hypothesized that culture‐directed treatment of bacteriobilia would decrease the incidence of infectious complications following pancreaticoduodenectomy. Methods In a retrospective study of 197 pancreaticoduodenectomy patients, those in the control group (n = 128, 2005–2009) were given perioperative prophylactic antibiotics, whereas those in the treatment group (n = 69, 2009–2011) were continued on antibiotics until intraoperative bile culture results became available. Patients with bacteriobilia received 10 days of antibiotic treatment, which was otherwise discontinued in patients without bacteriobilia. Various complication rates were compared using Fisher's exact test for categorical variables, Wilcoxon rank sum test for ordinal variables, and a two‐sample t‐test for continuous variables. Results Demographics, comorbidities, baseline clinical characteristics, and intraoperative and postoperative variables were similar between the two groups. There were higher incidences of elevated creatinine (19% versus 4%; P = 0.004) and preoperative hyperglycaemia (18% versus 7%; P = 0.053) in the control group. Fewer patients in the control group underwent preoperative biliary stenting (48% versus 67%; P = 0.017) and intraperitoneal drains were placed at the time of resection more frequently in the control group (85% versus 38%; P < 0.001). Bacteriobilia was found in 59% of patients. Treatment of bacteriobilia was associated with a decrease in the rate of postoperative wound infections (12% in the control group versus 3% in the treatment group; P = 0.036) and overall complication severity score (1 in the control group versus 0 in the treatment group; P = 0.027). Conclusions Prolonged antibiotic therapy for bacteriobilia may decrease postoperative wound infection rates after pancreaticoduodenectomy. A randomized prospective trial is warranted to provide evidence to further support this practice.